Effects of Subminimum Inhibitory Concentrations of Antibiotics on the Pasteurella multocida Proteome: A Systems Approach. (3rd March 2008) - Nanduri, Bindu; Lawrence, Mark L.; Peddinti, Divya Swetha; Burgess, Shane C.
Abstract : To identify key regulators of subminimum inhibitory concentration (sub-MIC) antibiotic response in the Pasteurella multocida proteome, we applied systems approaches. Using 2D-LC-ESI-MS 2, we achieved 53% proteome coverage. To study the differential protein expression in response to sub-MIC antibiotics in the context of protein interaction networks, we inferred P. multocida Pm70 protein interaction network from orthologous proteins. We then overlaid the differential protein expression data onto the P. multocida protein interaction network to study the bacterial response. We identified proteins that could enhance antimicrobial activity. Overall compensatory response to antibiotics was characterized by altered expression of proteins involved in purine metabolism, stress response, and cell envelope permeability.